Global, regional and seasonal analysis of total ozone trends derived from the 1995–2020 GTO-ECV climate data record - Coldewey-Egbers, Melanie; Loyola, Diego; Lerot, Christophe; Van Roozendael, Michel (Atmospheric Chemistry and Physics, 2022)
We present an updated perspective on near-global total ozone trends for the period 1995–2020. We use the GOME-type (Global Ozone Monitoring Experiment) Total Ozone Essential Climate Variable (GTO-ECV) satellite data record which has been extended and generated as part of the European Space Agency's Climate Change Initiative (ESA-CCI) and European Union Copernicus Climate Change Service (EU-C3S) ozone projects. The focus of our work is to examine the regional patterns and seasonal dependency of the ozone trend. In the Southern Hemisphere we found regions that indicate statistically significant positive trends increasing from 0.6 ± 0.5(2σ) % per decade in the subtropics to 1.0 ± 0.9 % per decade in the middle latitudes and 2.8 ± 2.6 % per decade in the latitude band 60–70∘ S. In the middle latitudes of the Northern Hemisphere the trend exhibits distinct regional patterns, i.e., latitudinal and longitudinal structures. Significant positive trends (∼ 1.5 ± 1.0 % per decade) over the North Atlantic region, as well as barely significant negative trends (−1.0 ± 1.0 % per decade) over eastern Europe, were found. Moreover, these trends correlate with long-term changes in tropopause pressure. Total ozone trends in the tropics are not statistically significant. Regarding the seasonal dependence of the trends we found only very small variations over the course of the year. However, we identified different behavior depending on latitude. In the latitude band 40–70∘ N the positive trend maximizes in boreal winter from December to February. In the middle latitudes of the Southern Hemisphere (35–50∘ S) the trend is maximum from March to May. Further south toward the high latitudes (55–70∘ S) the trend exhibits a relatively strong seasonal cycle which varies from 2 % per decade in December and January to 3.8 % per decade in June and July.